2021
DOI: 10.1021/acs.chemmater.0c04385
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution in Iron-Catalyzed Graphitization of Hard Carbons

Abstract: Despite the recent interest in catalytic graphitization to obtain graphite-like materials from hard-carbon sources, many aspects of its mechanism are still poorly unknown. We performed a series of in situ experiments to study phase transformations during graphitization of a hard-carbon precursor using an iron catalyst at temperatures up to 1100 °C and ex situ total scattering experiments up to 2000 °C to study the structural evolution of the resulting graphitized carbon. Our results show that upon heating and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…For example, in situ synchrotron XRD data from Gomez-Martin et al showed that the onset of graphitization of a wood precursor corresponded to the appearance of an Fe 3 C phase. 222 During cooling, the Fe 3 C phase transforms to γ-Fe then α-Fe, triggering a second carbon precipitation step. This change in the crystalline composition on cooling highlights the importance of studying graphitization in situ .…”
Section: Mechanism Of Catalytic Graphitizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in situ synchrotron XRD data from Gomez-Martin et al showed that the onset of graphitization of a wood precursor corresponded to the appearance of an Fe 3 C phase. 222 During cooling, the Fe 3 C phase transforms to γ-Fe then α-Fe, triggering a second carbon precipitation step. This change in the crystalline composition on cooling highlights the importance of studying graphitization in situ .…”
Section: Mechanism Of Catalytic Graphitizationmentioning
confidence: 99%
“…216 Fe and Fe 3 C are both phases that are commonly iden-tied in in situ X-ray diffraction studies of iron-catalyzed graphitization, oen within the same sample. 146,149,222,223 This raises the possibility that both dissolution-precipitation and carbide decomposition are potential mechanisms in catalytic graphitization. However, other pathways may also be possible.…”
Section: The Chemical Nature Of the Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by taking into account the higher chemical potential of amorphous carbon compared with graphite, Parmon showed such a high carbon solubility into the metal particles is thermodynamically favorable and could result in a meta-stable carbide melt forming at the surface . A finding supported by other studies on Au and mixed Co/Fe nanoparticles; , and recently by in situ XRD of growth around iron particles …”
Section: Introductionmentioning
confidence: 75%
“…Despite the success of these models in explaining many experimental observations, more recent in-situ experiments, have detected graphitic carbon formation during heating rather than upon cooling as expected from the dissolution/precipitation mechanism. High-resolution transmission electron microscopy performed in situ has shown graphenic layers forming around metal particles at 500 °C; and X-ray diffraction (XRD) shows graphitic carbon formation around 700 °C. , A surface-mediated rearrangement of carbon into graphitic carbon is clearly more significant than precipitation; especially on smaller metal particles that do not behave as bulk materials, and operating at lower temperatures is more attractive for scalable production.…”
Section: Introductionmentioning
confidence: 99%